The Influence of Job Satisfaction, Organizational Commitment and Compensation on Employee Turnover Intention of PT Prima Mitra Multikarya - Novi Rokhmawati; Roziana Hidayati (Indonesian Vocational Research Journal, 2024)
Study This aim For know Influence Satisfaction Work , Commitment Organization and Compensation To Turnover Intention PT employees . Prima Mitra Multikarya . Deep sample study This use method sample fed up that is with use all employees totaling 59 employees at the PT. Prima Mitra Multikarya Office . Data analysis techniques using analysis multiple linear regression using SPSS version 24. Results of multiple linear analysis prove satisfaction work , commitment organization and compensation influential Partial to turnover intention employee at PT. Prima Mitra Multikarya . Satisfaction Work proven with output where tcount > ttable (3,290 > 2,002) with mark significant 0.002 < 0.05. Commitment organization proven with output where tcount > ttable (3,204 > 2,002) with mark significant 0.002 < 0.05. Compensation proven with output where tcount > ttable (3,334 > 2,002) with mark significant 0.002 < 0.05 Research results This showing that in a way Partial can concluded satisfaction work , commitment organization and compensation influential positive significant to turnover intention employee at PT. Prima Mitra Multikarya .